The Use of Laras in Contemporary Gamelan Music - Gunawan, Iwan; Milyartini, Rita; Masunah, Juju (Harmonia: Journal of Arts Research and Education, 2022)
Gamelan instruments, which have a distinctive tone system (scale) or are called laras, are a challenge for contemporary composers in their working techniques. In contrast to Western music which uses a “well-tempered” system, gamelan music has a distinctive phenomenon in its tone system, including the absence of standardization of basic notes and tone intervals. This article aims to analyze the concept of garap and the phenomenon of the use of laras) in contemporary gamelan music. The method used is content analysis, by taking four contemporary gamelan works that use the concept of garap on the use of a new scale, which is auditorily difficult to identify the scales in conventional musical knowledge. The content used is in the form of audio recordings and notations, which are then analyzed by various parametric musical aspects. The results show that there were two directions of garap on the tone systems (scale) in contemporary gamelan music. First, the direction of the garap is done by limiting the tones of the tone systems used in constructing the sound both vertically and horizontally. As in Supanggah’s “Thongkleng,” only five of the seven notes are used in the laras pelog. Meanwhile, in Mack’s “Crosscurrent,” only four tones are used out of the five notes in the laras degung. The direction of the second interpretation is to expand the tone by mixing other tones to build the impression of a new tone. In O’Neil’s “Lesson of Garden” and Gunawan’s “Noname and Nothing,” there is a chromatic approach to melodic contours to obscure the impression of conventional tone. O’Neil focuses more on melodic tone processing, while in Gunawan’s work, the tone processing is more rhythmic and random.